ANALISIS ALTMAN Z-SCORE UNTUK MEMPREDIKSI KEBANGKRUTAN PADA PERBANKAN UMUM SYARIAH TAHUN 2013 – 2017 - Wahyu Candra Susilowati; Djoko Kristianto; Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study was conducted to predict bankruptcy in Islamic public banks registered at Bank Indonesia (BI) and the Financial Services Authority (OJK) for the period of 2013 - 2017 using the modified Altman Z-score method. The banks studied were 11 banks, namely Aceh Syariah Bank, BCA Syariah Bank, Bukopin Syariah Bank, Dubai Syariah Panin Bank, BRI Syariah Bank, Victoria Syariah Bank, Maybank Syariah Bank, Mega Syariah Bank, Mandiri Syariah Bank, BNI Syariah Bank, Muamalat Bank . Data analysis techniques in this study are the Altman Z-score method using 5 ratios, namely working capital to total asset ratio (X1), retained earnings to total asset ratio (X2), earnings before interest and taxes to total asset ratio (X3) , Book Value of Equity to Book Value of Liabilities (X4). The results showed that the financial condition of Islamic banks is in a healthy condition. This can be seen from the average value of Zscore Islamic banks in 2013 to 2017 the average value of zscore is above 2,60.